2001
DOI: 10.1117/12.436675
|View full text |Cite
|
Sign up to set email alerts
|

<title>Progress of the EUVL alpha tool</title>

Abstract: After the successful completion ofthe European program EUCLIDES'in which core competence for Extreme UltraViolet Lithography (EUVL) technology was generated, ASML (system integration), Carl Zeiss (optics), and their partners have entered the next phase ofthe program: design and realization of an exposure tool called the alpha tool (ct-tool). This tool should be completed in 2003, and will demonstrate 50-nm-node compliant imaging using full-field all-reflective four-times reducing optics, as well as high perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 6 publications
0
15
1
Order By: Relevance
“…8 has a configuration similar to that used in existing EUV lithographic tools with a numerical aperture of 0.25 [34,35]. However, our result shows that high-quality imaging can be obtained at the higher numerical aperture of 0.3 as well.…”
Section: Discussioncontrasting
confidence: 49%
“…8 has a configuration similar to that used in existing EUV lithographic tools with a numerical aperture of 0.25 [34,35]. However, our result shows that high-quality imaging can be obtained at the higher numerical aperture of 0.3 as well.…”
Section: Discussioncontrasting
confidence: 49%
“…ASML (system integration), Carl Zeiss (optics), and their partners began to design and realize an alpha exposure tool in 2001 [13] and installed alpha-demo (AD) EUVL exposure tools at IMEC and SEMATECH North in 2006. This was a symbolic event that showed that EUVL was advancing toward industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…The tool optics used six mirrors and 4× demagnifications. The maximum numerical aperture was designed to be 0.25 with a 50 nm resolution [13]. AD tool used a tin-discharge-produced plasma (DPP) EUV source [14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006 two Alpha Demo Tools (ADT) have been shipped to R&D facilities at IMEC (Belgium) and the University of Albany (CSNE, NY, USA) [3,4,5,6]. In 2010 ASML has started the shipments of the second generation EUV system, the NXE:3100, to customers around the world and covering all main lithographic segments (DRAM, FLASH, LOGIC, MPU) [1,2,10] Both the ADT and the NXE:3100 system utilize optics with an NA of 0.25.…”
Section: Introductionmentioning
confidence: 99%